2020
DOI: 10.1101/2020.08.16.250084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell surface fluctuations regulate early embryonic lineage sorting

Abstract: In development, lineage segregation of multiple lineages must be coordinated in time and space. An important example is the mammalian inner cell mass (ICM), in which the primitive endoderm (PrE, founder of the yolk sac) physically segregates from the epiblast (EPI, founder of the foetus). The physical mechanisms that determine this spatial segregation between EPI and PrE are still poorly understood. Here, we identify an asymmetry in cell-cell affinity, a mechanical property thought to play a significant role i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…These cells have been generated and kindly given to us by Ian Rosewell (Francis Crick Institute, under Holger Gerhardts project license). Dox-inducible IRES mCherry Ezrin_CA & RhoA_CA ES ( Yanagida et al., 2020 ) cells were kindly given to us by Ayaka Yanagida from the Chalut and Nichols’s lab. The EZR_CA was engineered using a PiggyBac system with E14 ES cells.…”
Section: Methodsmentioning
confidence: 99%
“…These cells have been generated and kindly given to us by Ian Rosewell (Francis Crick Institute, under Holger Gerhardts project license). Dox-inducible IRES mCherry Ezrin_CA & RhoA_CA ES ( Yanagida et al., 2020 ) cells were kindly given to us by Ayaka Yanagida from the Chalut and Nichols’s lab. The EZR_CA was engineered using a PiggyBac system with E14 ES cells.…”
Section: Methodsmentioning
confidence: 99%
“…5I). Overall, this suggests DP nEnd is a good model for blastocyst stage PrE just prior to commitment 32,60 .…”
Section: B C)mentioning
confidence: 83%
“…Although this mechanism escapes the limitations of morphogens, there is no in-depth study on how cells move physically and the source of driving force. A computational model of cell sorting indicated that the asymmetric affinity between EPI and PrE cells is not enough to complete spatial isolation in mouse embryos 28, 29 . Our results show that in addition to the differential adhesion between EPI and PrE cells, energy input mediated by the mechanical vibration of the cavity is required to complete the segregation of the spatial location.…”
Section: Discussionmentioning
confidence: 99%